Repeated sprint ability in young basketball players: one vs. two changes of direction (Part 1) - Padulo, J.; Laffaye, G.; Haddad, M.; Chaouachi, A.; Attene, G.; Migliaccio, G. M.; Chamari, K.; Pizzolato, F. (Journal of Sports Sciences, 2015)
The present study aimed to compare the changes of direction on repeated sprint ability (RSA) vs. intensive repeated sprint ability (IRSA) protocols in basketball. Eighteen young male basketball players performed on RSA [10 × 30-m (15 + 15-m, one change of direction)] and IRSA [10 × 30-m (10 + 10 + 10-m, two changes of direction)]. A correlation matrix between RSA, IRSA, "squat jump (SJ)-countermovement jump (CMJ)", footstep analysis and total distance in Yo-Yo intermittent recovery level 1 was performed. The best time, worst time, total time and the number of footsteps were significantly smaller in the RSA test compared to IRSA test (P < 0.001), even though they were significantly correlated with each other (r > 0.80, P < 0.05). Blood lactate level and fatigue index did not show any difference between tests. The sensibility of the two tests assessed by the Bland-Altman analysis revealed a small bias (<1.5%) for almost all variables. Moreover, almost all time variables of the two tests were significantly correlated with the SJ (r > 0.478, P < 0.05), CMJ (r > 0.515, P < 0.05) and Yo-Yo (r > 0.489, P < 0.05) performances. The IRSA provided a reliable method for assessing specific sprint ability (with 10-m legs for IRSA ~2.3 s vs. 15 m for RSA ~3 s) with a closer link to basketball game`s actions (~2 s). Besides, IRSA could be an appropriate choice for assessing both RSA and changes of direction capacities in basketball players.